Micropulse laser therapy in chronic idiopathic central serous chorioretinopathy in right eye of 38-year-old patient - case report - Maciej Michalik; Krzysztof Marcinkowski; Dominika Hennik; Sebastian Sirek (Śląski Uniwersytet Medyczny w Katowicach, 2024)
INTRODUCTION: Central serous chorioretinopathy (CSC) is a disease characterized by idiopathic serous elevation of the sensory layer of the retina in the proximity of the macula. This phenomenon predominantly manifests unilaterally, particularly in young males who exhibit increased susceptibility to stress. The optimal treatment strategy for CSC remains questionable due to a diverse range of symptoms, variable clinical courses, an overall limited understanding of CSC's pathophysiology and a lack of consensus on classification systems. Recently, there has been growing adoption of micropulse laser therapy in CSC treatment, allowing targeted action on retinal pigment epithelium, without causing damage to nearby photoreceptors. The aim was to evaluate the use of micropulse laser therapy in chronic CSC. DESCRIPTION AND RESULTS: A 38-year-old patient with recurrent CSC in the right eye, previously treated locally with eye drops and oral medication for over a year, underwent evaluation. At the time of diagnosis, the patient exhibited a visual acuity of 0.63, intraocular pressure of 19 mmHg, and a central retinal thickness of 530 µm, as measured by optical coherence tomography (OCT). Fluorescein angiography (FA) confirmed the diagnosis, leading to the qualification for retinal micropulse laser therapy. Following the treatment, a subsequent FA test revealed improvement in the patient's clinical condition, with a vision acuity of 1.0 and intraocular pressure reduced to 17 mmHg. Additionally, the central retinal thickness measured by OCT decreased to 299 µm. CONCLUSIONS: The use of micropulse laser therapy demonstrates the potential to achieve sustainable clinical effects in patients with recurrent CSC.